A Challenging Diagnosis of Atypical Glut1-DS: A Case Report and Literature Review - Yu, Miaomiao; Miao, Jing; Lv, Yudan; Wang, Xue; Zhang, Wuqiong; Shao, Na; Meng, Hongmei (Frontiers in Neurology, 2021)
Glucose transporter type 1 deficiency syndrome (Glut1-DS) is a rare neurometabolic disorder caused by mutations of the SLC2A1 gene. Paroxysmal exercise-induced dyskinesia is regarded as a representative symptom of Glut1-DS. Paroxysmal non-kinesigenic dyskinesia is usually caused by aberrations of the MR1 and KCNMA1 genes, but it also appears in Glut1-DS. We herein document a patient with Glut1-DS who suffered first from paroxysmal exercise-induced dyskinesia and subsequently paroxysmal non-kinesigenic dyskinesia and experienced a recent worsening of symptoms accompanied with a low fever. The lumbar puncture result showed a decreased glucose concentration and increased WBC count in CSF. The exacerbated symptoms were initially suspected to be caused by intracranial infection due to a mild fever of less than 38.0° C, decreased cerebrospinal fluid (CSF) glucose and increased CSF white blood cell (WBC) count. However, the second lumbar puncture result indicated a decreased glucose concentration and normal WBC count in CSF with no anti-infective agents and the patient’s symptom did not relieve apparently. The continuous low glucose concentration attracted our attention and gene analysis was performed. According to the gene analysis result, the patient was diagnosed with Glut1-DS finally. This case indicates that the complex paroxysmal dyskinesia in Glut1-DS may be confusing and pose challenges for accurate diagnosis. Except intracranial infection, Glut1-DS should be considered as a differential diagnosis upon detection of a low CSF glucose concentration and dyskinesia. The case presented here may encourage clinicians to be mindful of this atypical manifestation of Glut1-DS in order to avoid misdiagnosis.